EMPOWERING TEENAGERS AND ADOLESCENT CADRES TO PREVENT EARLY MARRIAGE AS A RISK FACTOR FOR STUNTING INCIDENTS - Supriadi, Rizky Febriyanti; Ahmady, Ahmady (Poltekkes Kemenkes Kendari, 2025)
Early marriage is one of the indirect factors causing stunting in children. This is because early marriage not only impacts a mother's physical readiness but also her psychological state, which can affect child-rearing practices. In Mamuju Regency, the prevalence of early marriage is quite high, ranking second at 14.28%. Early marriage remains a common occurrence and an ongoing trend. Additionally, there is a lack of knowledge among adolescents regarding adolescent reproductive health, and insufficient monitoring and identification of adolescent reproductive health issues. The proposed solution is to increase adolescents' knowledge through education and mentoring programs on adolescent reproductive health. The implementation method involves conducting education and training for adolescent cadres on adolescent health and conducting adolescent reproductive health examinations using a peer education method. The results of this community service activity showed an increase of more than 40% in participants' knowledge of stunting and the impacts of early marriage. The health monitoring of adolescent girls identified 13 out of 62 female students who experienced anemia, and 2 female students who had menstrual disorders. The sustainability of this community service activity is achieved through adolescent cadres conducting peer education to all adolescents in Kelurahan Bebanga